Evidence in Practice: A Study of “Evidence-Based” Non-Formal Education - Thomas Archibald (Adult Education Research Conference, 2014)
Non-formal education programs are under increasing pressure to be “evidence-based,” where evidence derived from randomized controlled trials is seen as the most credible type of evidence—the “gold standard.” This qualitative study explores the politics of evidence enacted in the practices of the “evidencebased” education movement, focusing on three cases.